2020
DOI: 10.14202/vetworld.2020.2028-2032
|View full text |Cite
|
Sign up to set email alerts
|

Ocimum sanctum Linn. ethanolic extract inhibits angiogenesis in human lung adenocarcinoma (a549) cells

Abstract: Background and Aim: Ocimum sanctum (OS) is a herbal plant, which is easy to find and is widely used as an alternative medication. The previous studies have shown that several species of OS extract have therapeutic properties, and in some cases, antitumor properties. Furthermore, several data have shown the antiproliferative effects of OS extract in cases of breast cancer, human fibrosarcoma, and oral cancer. Lung adenocarcinoma is a major cause of male cancer worldwide; however, the effect of OS (of Indonesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Consequently, inhibition of migration and angiogenesis of A549 cells were observed. As a result, OS ethanol extract is suggested as a potential application of pulmonary metastasis treatment [ 47 ]. Breeta et al reported that the Thuja orientalis L. extract at different concentrations has the ability to inhibit the cancer cell growth and progression by inhibiting angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, inhibition of migration and angiogenesis of A549 cells were observed. As a result, OS ethanol extract is suggested as a potential application of pulmonary metastasis treatment [ 47 ]. Breeta et al reported that the Thuja orientalis L. extract at different concentrations has the ability to inhibit the cancer cell growth and progression by inhibiting angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have revealed the potential of EEOS as an anticancer drug candidate. EEOS can induce apoptotic activity through the mitochondrial pathway 12 and inhibit angiogenesis of the human lung adenocarcinoma cell line A549, 13 EEOS inhibits invasion and reduces the activity of MMP-2 and MMP-9 HN4 and carcinoma head and neck squamous cells HN12, 16 EEOS has cytotoxic ability against leukemia cells K562 17 and oral cancer cell line Ca9-22. 18 In this study, EEOS demonstrated a significant antiproliferative effect against the MCF-7 and T47D human breast carcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, relatively few studies have investigated the biological activity underlying the cytotoxic effect of EEOS treatment in altering the survival of lung adenocarcinoma A549 cells through the synergistic induction of apoptosis signaling via the intrinsic mitochondrial pathway, 12 the ethanolic extract of OS inhibited A549 cell angiogenesis by how to reduce the expression of αvβ3 integrins, MMP-2, and MMP-9. 13 To provide scientific justification for the use of herbal medicines, it is necessary to record and publish preclinical evidence and clinical-based research. Therefore, this study was designed to analyze the ability of the ethanolic extract of O. sanctum Linn leaves as an anticancer agent in breast cancer cells, mainly to prove the ability to inhibit the proliferation of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed the potential of EEOS as an anticancer drug candidate. EEOS can induce apoptotic activity through the mitochondrial pathway 12 and inhibit angiogenesis of the human lung adenocarcinoma cell line A549, 13 EEOS inhibits invasion and reduces the activity of MMP-2 and MMP-9 HN4 and carcinoma head and neck squamous cells HN12, 16 EEOS has cytotoxic ability against leukemia cells K562 17 and oral cancer cell line Ca9-22. 18 In this study, EEOS demonstrated a significant antiproliferative effect against the MCF-7 and T47D human breast carcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, relatively few studies have investigated the biological activity underlying the cytotoxic effect of EEOS treatment in altering the survival of lung adenocarcinoma A549 cells through the synergistic induction of apoptosis signaling via the intrinsic mitochondrial pathway, 12 the ethanolic extract of OS inhibited A549 cell angiogenesis by how to reduce the expression of αvβ3 integrins, MMP-2, and MMP-9. 13 To provide scientific justification for the use of herbal medicines, it is necessary to record and publish preclinical evidence and clinical-based research. Therefore, this study was designed to analyze the ability of the ethanolic extract of O. sanctum Linn leaves as an anticancer agent in breast cancer cells, mainly to prove the ability to inhibit the proliferation of cancer cells.…”
Section: Introductionmentioning
confidence: 99%